Selenium and RNA Virus Interactions: Potential Implications for SARS-CoV-2 Infection (COVID-19) - Hiffler, Laurent; Rakotoambinina, Benjamin (Frontiers in Nutrition, 2020)
SARS-CoV-2 is an RNA virus responsible for the COVID-19 pandemic that already claimed more than 340,000 lives worldwide as of May 23, 2020, the majority of which are elderly. Selenium, a natural trace element, has a key and complex role in the immune system. It is well documented that Selenium deficiency is associated with higher susceptibility to RNA viral infections and more severe disease outcome. In this article, we firstly present evidence on how Selenium deficiency promotes mutations, replication and virulence of RNA viruses. Next, we review how Selenium might be beneficial via restoration of host antioxidant capacity, reduction of apoptosis and endothelial cell damages as well as platelet aggregation. It also appears that low Selenium status is a common finding in conditions considered at risk of severe COVID-19, especially in the elderly. Finally, we present a rationale for Selenium use at different stages of COVID-19. Selenium has been overlooked but may have a significant place in COVID-19 disease spectrum management, particularly in vulnerable elderly, and might represent a game changer in the global response to COVID-19.